The Development of Semi-Auto Flood Door Barrier - Khairi Supar; Sheikh Ismail, Sheikh Mohammad Naqib; Azmi, Muhammad Azammudin; Jafri, Ariff Izzudin; Mohamad Azim Mohammad Azmi; Hilton Ahmad (Multidisciplinary Applied Research and Innovation, 2024)
Flood barriers play a crucial role in mitigating the devastating impact of flooding events. This project focuses on the testing of flood barriers to enhance their effectiveness and reliability. Recent destructive floods in the Czech Republic have highlighted the urgent need for flood mitigation strategies to minimize fatalities and property damage. Flood control techniques aim to confine water outside inhabited areas while facilitating the rapid drainage of populated regions. To ensure the optimal performance of new flood barriers, multiple standardized tests must be conducted during their development. Numerical simulations are essential for predicting the behavior of these barriers, aiding in their design process. This study specifically investigates the feasibility and affordability of temporary flood barriers (TFBs) in reducing the severe consequences of flooding on exposed highways. TFBs are physical structures erected along the edges of houses to prevent water from inundating them during flood events. They serve to minimize property damage and enable the uninterrupted operation of roads even in flood-prone areas. The study encompasses a discussion of successful TFB applications, along with an overview of the various types of TFBs available in the market, including their associated advantages and limitations. By exploring the potential of TFBs and examining their suitability as a flood mitigation strategy, this research aims to contribute to the development of effective flood control measures.